Dampak Stigma terhadap Kesejahteraan Psikologis Keluarga yang Merawat Orang dengan Gangguan Jiwa di Kabupaten Pamekasan - Willi Holis; Ida Wahyuni; Ahmad Zaini Arif (Jurnal Sains dan Kesehatan, 2026)
Stigma toward people with mental disorders affects not only individuals living with mental illness but also the psychological well-being of family members who serve as their primary caregivers. Families often experience social rejection, discrimination, and negative stereotypes, which increase emotional and psychological burdens while reducing the quality of care they provide. This study aimed to explore the impact of stigma on the psychological well-being of families caring for people with mental disorders in Pamekasan Regency. A qualitative study using a phenomenological approach was conducted involving 11 participants selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis to identify participants' lived experiences. The findings revealed one overarching theme, namely the negative impact of stigma, which consisted of three categories: effects on family members, family relationships, and patients. Stigma generated feelings of sadness, anxiety, psychological distress, sleep disturbances, social withdrawal, family conflicts, and changes in family interactions with patients. These experiences negatively influenced caregivers’ emotional well-being and their ability to provide optimal support for family members with mental disorders. The study concludes that stigma has a substantial adverse impact on the psychological well-being of family caregivers and the quality of care provided to people with mental disorders. Therefore, comprehensive interventions focusing on stigma reduction, community education, and strengthening psychosocial support systems are essential to improve family resilience and promote better mental health outcomes.